Natural Killer Cells in SARS-CoV-2-Vaccinated Subjects with Increased Effector Cytotoxic CD56dim Cells and Memory-Like CD57+NKG2C+CD56dim Cells - Gentili, Valentina; Bortolotti, Daria; Morandi, Luca; Rizzo, Sabrina; Schiuma, Giovanna; Beltrami, Silvia; Casciano, Fabio; Papi, Alberto; Contoli, Marco; Zauli, Giorgio; Rizzo, Roberta (Frontiers in bioscience (Landmark. Print), 2023)
Background: The infection and negative effects of the SARS-CoV-2 (severe acute respiratory syndrome coronavirus) virus are mitigated by vaccines. It is unknown whether vaccination has worked by eliciting robust protective innate immune responses with high affinity. Methods: Twenty healthy volunteers received three doses of Comirnaty (Pfizer Australia Pty Ltd.) and were evaluated 9 months after the second vaccination and 1 month after the booster dose. The exclusion criteria were the presence of adverse effects following the vaccination, a history of smoking, and heterologous immunization. The inclusion criteria were the absence of prior Coronavirus Disease (COVID)-19 history, the absence of adverse effects, and the absence of comorbidities. Specific phenotype and levels of CD107a and granzyme production by blood NK (natural killer) cells were analyzed after exposure to SARS-CoV-2 spike antigen (Wuhan, Alpha B.1.1.7, Delta B.1.617.2, and Omicron B1.1.529 variants), and related with anti-SARS-CoV-2 antibody production. Results: The booster dose caused early NK CD56dim subset activation and memory-like phenotype. Conclusions: We report the relevance of the innate immune response, especially NK cells, to SARS-CoV-2 vaccines to guarantee efficient protection against the infection following a booster dose.